Comparison of Students' Critical Thinking Abilities Using Project-Based Learning Cycle Models and Conventional Models - Mayasari; Syuhada, Siti; Arief, Hidayatul (Eduscape : Journal of Education Insight, 2024)
This Exploration began eith a learning problem in the economic education course, a problem that’s known so far is that the learning process is pupil-centred, but the learning conditioning carried out are limited to group donations followed by conversation and debates with no follow-up. Closes with the lecture’s evidence, where learning becomes monotonous. For this reason, there’s a need for invention in learning to ameliorate this situation by using a design project-based learning cycle model compared to conventional models. This research uses quantitative methods with a pure experimental approach (true experimental design). A total of 115 students as a population were taken using simple random sampling techniques. So, the exploration sample for the experimental class (R002) was 58 scholars and the control class (R001) was 57 scholars. Pretest-Posttest Group Design as a data analysis tool in this exploration. The exploration that has been conducted shows the results: 1) There’s a description of the differences in scholars’ critical thinking capacities prior to and after using the design project based learning cycle model in educational economics courses; 2) There’s a description of scholars' critical thinking capasities prior to and after using conventional learning models in educational economics courses; 3) oroginal critical thinking capacities show that scholars’ critical thinking capacities prior to using the project based learning cycle model and conventional learning models in educational economics courses are significantly different; and 4) Final critical thinking capacities which show scholars’ critical thinking abilities after using the project based learning cycle model and conventional learning models in educational economics courses are significantly different.